Relationships between positive schemas and life satisfaction in psychiatric inpatients - Chi, Danni; Zhong, Haiyun; Wang, Yubo; Ma, Hong; Zhang, Yuanyuan; Du, Xiangju (Frontiers in Psychology, 2022)
Introduction Unlike the extensively examined early maladaptive schemas, positive schemas have rarely been examined in psychiatric patients. This study aimed to investigate the relationships between anxiety, depression, life satisfaction, resilience, and positive schemas in psychiatric inpatients with generalized anxiety disorder or major depressive disorder and explore their associations. A sample of 140 psychiatric inpatients with anxiety and depression, aged between 18 and 72 years (Mage = 35.62, SD = 13.87) participated in this study. Methods A majority were women (n = 98, 70.0%). The analyses examined resilience and anxiety/depression as mediators between positive schema and life satisfaction. Results Based on statistical analyses, resilience and anxiety/depression were parallel rather than serial mediators between positive schemas and life satisfaction. These results confirmed the positive association between positive schemas and life satisfaction, and identified mechanisms between them: directly associated and indirectly associated through the parallel mediations of resilience and anxiety/depression. Discussion The findings of this study suggest that higher levels of positive schemas in psychiatric inpatients are associated with greater life satisfaction directly and through the mediation of reduced psychopathological emotions and increased resilience. Longitudinal studies are needed to explore the associations between positive schemas and negative and positive outcomes and the mechanisms underlying these associations in clinical populations.